Nurturing compassion in neonatal end-of-life care: a qualitative exploration of palliative care nurses’ roles and experiences - Osama Mohamed Elsayed Ramadan; Alaa Hussain Hafiz; Nouran Essam Katooa; Nasreen M. Alghamdi; Nadia Bassuoni Elsharkawy; Enas Mahrous Abdelaziz; Nermen Abdelftah Mohamed; Nagwa Ibrahim Mabrouk Baraka (BMC Nursing)
Abstract Background Compassion is central to neonatal end-of-life care, ensuring comfort and dignity for neonates with life-limiting conditions and their families. However, the emotional and ethical challenges faced by neonatal palliative care nurses, particularly in culturally diverse settings, remain underexplored, limiting the development of effective support mechanisms. Aim This study aims to explore the lived experiences of neonatal palliative care nurses in Egypt, focusing on how they cultivate and sustain compassion in end-of-life care. It examines the role of compassion in shaping caregiving practices, ethical decision-making, and coping with emotional distress. Additionally, it investigates the cultural and institutional facilitators and barriers that influence compassionate care delivery, generating evidence-based recommendations for nursing education, practice, and policy. Methods A qualitative phenomenological study guided by Interpretative Phenomenological Analysis (IPA) was conducted. Forty nurses from four neonatal intensive care units (NICUs) in Egypt completed semi-structured interviews and reflective journaling. Data were analyzed using a two-phase approach, incorporating Lazarus and Folkman’s Transactional Model of Stress and Coping to contextualize findings within broader emotional regulation and resilience frameworks. Results Analysis yielded seven themes. Nurses reported developing deep emotional bonds with neonates and families, which enhanced care quality but also intensified personal grief and ethical dilemmas. Compassion emerged as a key mechanism for facilitating empathetic communication and holistic care, yet sustaining it was hindered by compassion fatigue, high workloads, insufficient training, and cultural expectations complicating end-of-life decision-making. Conclusion Compassion is crucial in mitigating neonatal palliative care nurses’ emotional and ethical burdens. To sustain compassionate care, robust institutional support, culturally responsive training, and interdisciplinary collaboration are essential. These findings inform nursing education, policy, and practice, emphasizing strategies to enhance nurse well-being and improve care quality in diverse healthcare settings. Implications for Practice Strengthening institutional policies, integrating resilience training, and developing culturally sensitive communication strategies are critical to ensuring sustainable, compassionate care in neonatal palliative settings.